Mendialogkan Kehidupan Keagamaan - Thohir, Mudjahirin (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
In the social life, the religion have two faces: conflict and peace. Conflict arises in many reasons, one of them is ethnocentric views. Peace condition comes because all of religion advocates to living in harmony.  The two phenomena were studied  in the discussion of the religious leaders in the Organization of the Religious Harmony Forum (FKUB) Central Java.  Result of the workshop are: (1) to avoid conflict, do not take ethnocentric views; (2). The truth of religion is absolute in relative term; (3) the religious community must have  a principle that the different is beautiful; (4) the last but not lease, needed to form interfaith community in some areas with different religions.